EFFECTS OF MASSIVE TELENCEPHALIC LESIONS ON THE ORGANIZATION OF BEHAVIOR IN PIGEONS (COLUMBA-LIVIA) - Silva, A. L.; Ferrari, EAM (Associação Brasileira de Divulgação Científica (ABRADIC), 1991)
The effects of massive lesions of the telencephalon on the behavioral repertoire of captive pigeons were investigated. The behavior of four birds with an intact telencephalon was compared to that of four birds submitted to ablation of telencephalic structures. Behavioral audio recording was done according to previously defined categories in three daily sessions for fifteen days. Experimental birds were followed up for one month. Immediately after the lesion, operated birds showed decreases in the occurrence of different behaviors such as coordinated movements, feeding, interaction, preening, maintenance, exploration and vocalization and increases in locomotion and discrete movements of the body when compared to the control birds (P < 0.05). Recovery of exploration (P < 0.05), feeding and localization was observed during the follow-up period. These data are interpreted as suggestive of a functional role of the telencephalon in the organization of behavior and a long-term recovery of behavior after detelencephalation.
Keywords: TELENCEPHALON ABLATION; BEHAVIORAL RECOVERY; PIGEON BEHAVIOR